Juvenile periodontitis - Karin G. Dekker (Journal compilation 2007 Blackwell Munksgaard, 2007)
In May 2004, a 14-year-old boy visited a dentist for the first time. During this meeting the dentist executed a periodontal diagnosis and she found periodontal defects locally.